Biology of Plutella xylostella L. (Lepidoptera: Plutellidade) Reared on Cauliflower Genotypes - Chagas Filho, Norton R. [UNESP] (2010)
This work was conducted to evaluate biological parameters of Plutella xylostella L. reared on leaves of several cauliflower genotypes under laboratory conditions. The experiment was set in a randomized block design and arranged in a 6 x 2 factorial (genotypes x generations). Leaf disks of the cultivars Barcelona, Verona, Piracicaba Precoce, Sharon, Silver Streak, and Teresopolis Gigante were placed in Petri dishes with 12 newly-hatched larvae. Leaf disks were initially changed after the fourth day, but daily afterwards until the larvae reached the pupal stage. The same procedure was adopted for the second generation. Twenty adults of each sex were separated from each genotype to evaluate their longevity, and I 0 couples from each treatment were used to assess female fecundity. The lowest larval survival was obtained on the 'Silver Streak' (78.9%) and highest on 'Verona' (97.1%). The 'Silver Streak' and `Teresopolis Gigante' showed the lowest pupal weights (4.83 mg and 5.11 mg, respectively), as well as the lowest fecundity, 119.4 and 123.0 eggs/female, respectively, while 'Piracicaba Precoce' the highest (167.7 eggs/female). Males obtained from larvae reared on `Teresopolis Gigante' and 'Silver Streak' lived shorter (5.1 days), while the short-lived females were obtained from larvae reared on 'Barcelona' and 'Verona' (4.9 and 5.0 days). Insect development was prolonged in the second generation in all tested genotypes.